Retrieval of Total Scattering Cross Sections of Molecules from Inhomogeneously Broadened Absorption Lines - V. P. Kochanov; L. N. Sinitsa (Journal of Spectroscopy)
A new method of retrieving quantitative information on the hard, soft, and diffraction collision’s frequencies from inhomogeneously pressure-broadened line profiles was proposed and tested. The essence of the method lies in the processing of recorded profiles using various profiles’ models containing these frequencies treated as adjustable parameters in different manners. Three self-broadened H2O absorption lines free of an instrumental function were processed with the use of four model line profiles. Retrieved set of pressure line broadening and narrowing constants allows finding out the sought frequencies. The estimation of the total scattering cross section, ∼630 Å2, in pure water vapor was made.